The role of the Bali Province village community development service in increasing village potential - Sugiantiningsih, Anak Agung Putu (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2023)
The current study aims to unpack the role of the Bali Province Indigenous Community Promotion Service in Increasing Village Potential in Denpasar City and the extent of involvement of the Bali Province Indigenous Community Promotion Service in Increasing Village Potential in Denpasar City. A qualitative approach was employed to correspond to the portrayed problems due to the exploration of a descriptive analysis approach. This study, moreover, plotted observation, interviews, and documentation as the data collection procedures. The results unpacked the humongous role of the Bali Province Indigenous Community Promotion Service in Increasing Village Potential in Denpasar City, especially in realizing the vision and mission of the Bali Provincial government (Nangun Sad kerthi Loka Bali). The current study also recruited the Head of the Office for the Advancement of Indigenous Peoples of Bali Province, Bendesa Adat Pakraman Village Denpasar, and Bendesa MDA Denpasar City as the subjects of the study. The inhibiting factors can be overcome if good cooperation is established. In addition, the heterogeneity of the Denpasar City community leads to complicated potential raises in Denpasar's villages, Bali.